Aberrant orbitofrontal cortical activation interferes with encoding of Pavlovian fear conditioning - Sun, Chung-Fu; Chang, Chun-hui (Frontiers in Behavioral Neuroscience, 2022)
Obsessive-compulsive disorder (OCD) patients were usually found with the hyperactivation of the orbitofrontal cortex (OFC) and a deficit in fear extinction learning. The OFC can be subdivided into the lateral OFC (lOFC) and the medial OFC (mOFC). Previous studies have suggested that both subregions are involved in the modulation of negative emotions. However, how aberrant activation of the OFC interacts with the encoding of Pavlovian fear remains unknown. In this study, the lOFC or the mOFC was pharmacologically activated or inactivated before the fear conditioning on Day 1, followed by a context test on Day 2 and a tone test on Day 3 in male Long-Evans rats. We found that for the animals that underwent fear conditioning under aberrant activation of either the lOFC or the mOFC, they showed normal within-session fear expression. However, the acquisition/consolidation of contextual fear was impaired under mOFC activation, while the acquisition/consolidation of cued fear was impaired under either the lOFC or the mOFC activation, in that these animals showed lower freezing compared to controls during the retrieval test. On the other hand, for the animals that underwent fear conditioning under inactivation of either the lOFC or the mOFC, they showed normal within-session fear expression, as well as intact encoding of both the contextual and cued fear. Together, our results suggested that the OFC was not actively engaged in the acquisition of Pavlovian fear conditioning, but aberrant activation of the OFC impaired fear learning.